Oscillator tracking filter with nonlinear feedback - Menyalo, A.D.; Rapin, V.V. (Radiotekhnika, 2018)
An oscillator tracking filter based on a single circuit LC oscillator with the nonlinear feedback synchronized by a periodic nonharmonic signal is proposed. The theoretical investigation of the first-harmonic injection locked LC oscillator operation is considered. The model of the oscillator is presented and the stationary state operation is analyzed by the harmonic balance method. The obtained simple analytical expressions describing first and second harmonic components allow making quality analysis and can be directly applied to the practical design. This filter is intended for a selection of the first harmonic component of the external periodic polyharmonic signal in a wide working range with the purpose of measuring its frequency. It is found that such filters were very effective at large amplitudes of higher harmonic components of the external signal with unstable amplitude-phase correlations. Practical application has confirmed its high reliability.